Family impact and economic burden among caregivers of children with chronic kidney disease in Assiut, Egypt - Manal M Darwish; Shimaa Hosny Hassan; Samaher Fathy Taha; Hosnia Said Abd El-Megeed; Taghreed Abdul-Aziz Mohammad Ismail (SpringerOpen, 2020)
Abstract Background Chronic disease greatly increases children's dependency on parents/caregivers (usually mothers) as they face new problems associated with caring for a child with chronic disease. Thus, chronic kidney disease (CKD) presents a burden for children and their families that last throughout life in different aspects. This study aimed to assess family impact and economic burden of chronic kidney disease (CKD) in children on their families. Methods A cross-sectional study was carried out on 250 caregivers of children with CKD attending tertiary care hospital/health insurance clinics in Assiut, Egypt using PedsQL™ family impact module (FIM) for assessing family impact and economic burden between January and May 2018. Results Seventy six percent of caregivers shared paying for treatment with health insurance while 14% paid the total expenses out of their pockets. Although the majority (87.2%) of caregivers suffered different degrees of financial hardship, more than 60% of them had no coping strategy. The regression module showed that responding caregiver, degree of financial hardship, treatment modality, and socioeconomic class were significant predictors of total FIM (β = 0.38, P < 0.001; β = 0.28, P < 0.001; β = 0.22, P < 0.001; β = 0.13, P = 0.006 respectively). Conclusion Most caregivers were involved in paying for treatment of their children either totally or sharing with health insurance and suffered different degrees of financial hardship. Mothers, caregivers with great financial hardship, and caregivers of children on dialysis had the lowest scores of PedsQL™ FIM. There is a high need for expansion of health insurance umbrella to reduce financial hardship together with continued multidimensional support to families.